Facile synthesized zinc oxide nanorod film humidity sensor based on variation in optical transmissivity. Issue 13 (8th June 2022) - Verma, Rajni; Pathak, Saurabh; Dey, Kajal Kumar; Sikarwar, Samiksha; Yadav, B. C.; Srivastava, A. K.
Abstract : Variation in the transmitted light intensity from zinc oxide thin films with moisture content provides a great opportunity to use them for humidity sensing. Abstract : Variation in the transmitted light intensity from metal oxide thin films with moisture content provides a great opportunity to use them for humidity sensing. Herein, we have developed a novel and simple humidity sensor based on ZnO nanorod (ZNR) thin films which work as transmission-based sensing elements in an in-house fabricated sensing setup. The ZNR sensing element shows excellent linear sensing performance in the relative humidity (RH) range 10–90% and does not show any hysteresis. A maximum change in optical power of ∼95 μW is observed with the change in RH in the range 10–90%, for the sample with the smallest crystallite size (ZNR1) and highest pore diameter of the ZNR film. Also, a maximum sensitivity of 1.104 μW/% RH is observed for the ZNR1 sample which drops to 0.604 μW/% RH for the highest crystallite size sample (ZNR4). The presence of oxygen vacancies and the micro-porous nature of the film allow the absorption of water vapour on the film which deflects light at different angles that vary with the moisture content. The experimental results suggest that the ZNR film with a smaller crystallite size and larger pore diameter is more sensitive for humidity measurements. Further, an improved sensing performance is perceived in ZNRs because of the larger surface area of the nanorods. The ZNR based sensing elements do not suffer from ageing effects and exhibit high repeatability (88.74%). Further, the humidity sensor has a response time of 62 seconds and recovery time of 100 seconds which can be considered as a fairly quick response.